LITERASI STATISTIK DAN IMPLEMENTASINYA PADA OPTIMALISASI MICROSOFT EXCEL DALAM PEMBUATAN DAN PENGELOLAAN BANK SOAL - ANDREAS RONY WIJAYA; Muhammad Bayu Nirwana; Kiki Ferawati; Hasih Pratiwi; Respatiwulan Respatiwulan; Sri Sulistijowati Handayani; Yuliana Susanti; Frencilia Paulina Agustin; Aqila Khansa Hartanto; Bilqies Syafina Wardati (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
In today’s digital era, the integration of technology in education has become increasingly important. One key aspect that can be enhanced through technology is its application in teaching and learning activities. The use of technology enables the learning process to become more efficient. One such technology that can be applied is Microsoft Excel. Traditionally, Excel has been widely recognized as data processing software. In Karanganyar Regency, particularly within the Mathematics Teachers’ Working Group Forum (MGMP Matematika), teachers already possess basic skills in using Excel. Strengthening statistical literacy through the use of Excel among teachers is expected to improve the quality of teaching, enabling them to better understand, analyze, and present data. Until now, in the preparation and development of question banks, many teachers have created exam questions manually without taking advantage of technological tools. In fact, Excel provides features that can assist teachers in designing question banks in a more systematic, efficient, and organized manner. These features include the creation, categorization, and analysis of questions. As a discipline focused on data collection, analysis, and data-driven decision-making, statistics plays a vital role in enhancing society’s understanding of quantitative information. To promote statistical literacy, the Statistics and Data Science Research Group in the Field of Environment and Health, Department of Statistics, Faculty of Mathematics and Natural Sciences, Universitas Sebelas Maret, organized a community service program in the form of training for junior high school teachers in Karanganyar through the MGMP Matematika forum. The training aimed to optimize the use of Microsoft Excel in developing question banks, enabling teachers to design and manage questions more systematically and efficiently. Through this training, teachers are expected to apply data-based techniques in test item development to improve the effectiveness of learning evaluation.